Sustainable and Efficient Structural Systems for Tall Buildings: Exploring Timber and Steel–Timber Hybrids through a Case Study - Fabrizio Ascione; Francesco Esposito; Giacomo Iovane; Diana Faiella; Beatrice Faggiano; Elena Mele (Buildings, 2024)
The paper focuses on tall timber buildings. The major aim of this paper is to identify the most sustainable and efficient structural system to increase the height of timber buildings, also considering steel–timber hybrid structures. First of all, a brief review of tall buildings’ evolution is presented to understand why tall timber buildings are considered nowadays and which are the most adopted structural solutions. Then, the case study of the tallest timber building in the world is selected and utilized as an archetype. Once the model has been validated, seven alternative structural systems are considered by varying the horizontal load resisting system and preserving the same member cross-sections as the reference building. The variants are tested and compared in terms of material consumption, vibration characteristics and lateral load response. Using the best structural system, the height of the building is increased, pushing the structures beyond the current limits and identifying the most efficient option. The idea is to preserve the column cross-sections and balance the increase in gravity loads due to the additional floors by replacing the concrete floors with timber counterparts. With the same structural system, equivalent steel–timber hybrid solutions are finally tested and compared in terms of sustainability to timber-only counterparts and to the original project. The results of analyses show that the use of steel elements combined with timber can lead to optimized and sustainable structural solutions.